Charged amino acids as spectroscopic determinants for chlorophyll in vivo - Eccles, Joseph (1983)
In this paper we propose that the large spectroscopic red shifts observed for chlorophyll (Chl) and bacteriochlorophyll (BChl) in vivo may be due to charged amino acids in the binding site. Molecular orbital calculations of the transition energies of Chl in the field of external charges are carried out. The calculated wavelength shifts induced by these charges are comparable in magnitude to those observed in vivo. Moreover the size of the shifts increases in the order BChl b > BChl a > Chl a, which is the observed trend. The ability of the calculations to account for both the absolute and relative magnitudes of the wavelength shifts argues for the validity of the model. Further indirect support comes from the recent demonstration that charged amino acids are responsible for the colors of visual pigments and bacteriorhodopsin. In addition to their effects on spectra the presence of external charges induces large changes in the ionization potential of Chl molecules and thus might explain the in vivo alteration of the oxidation potentials in reaction centers.